The Influence of e-Office Quality on Intention to Use it in Managing Maritime Documents at KSOP Utama Tanjung Perak - Ramadhan, Febrianto; Yuhana, Umi Laili; Amaliah, Bilqis (IPTEK The Journal for Technology and Science, 2024)
This research discusses the intention to use e-office applications for managing maritime documents at the Tanjung Perak Harbormaster and Main Port Authority (KSOP) Office. As an application in government agencies, E-Office is very important in speeding up information, increasing performance, productivity, and ease of implementation. This research aims to determine the influence of e-office quality on intentions to use e-office technology at KSOP Utama Tanjung Perak. This method combines the Technology Acceptance Model (TAM) andWebqual techniques. TAM is used to measure users’ perceived acceptance of technology, which consists of 4 constructs: Perceived Effectiveness (PU), Attitude Toward Use (ATU), Perceived Ease of Use (PEOU), and Behavioral Intention to Use (BIU). The WebQual method for measuring the influence of quality consists of 3 dimensions: Usability, Information Quality, and Service Interaction Quality. Perceived Ease of Use (PEOU) and Usability are the most influential quality variables. The t-test results: Perceived Ease of Use influences the intention variable 3.152, Attitude Toward Use influences behavioral choices 2.723, Usability influences intention to use 3.588. This research is significant for measuring the quality of e-offices, which can also be used as a reference/ evaluation in developing e-office applications at KSOP Main Tanjung Perak.